2003
DOI: 10.1080/07391102.2003.10506887
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Thermodynamic Studies on the Binding of Sanguinarine and Berberine to Triple and Double Helical DNA and RNA Structures

Abstract: A comparative study on the interaction of sanguinarine and berberine with DNA and RNA triplexes and their parent duplexes was performed, by using a combination of spectrophotometric, UV thermal melting, circular dichroic and thermodynamic techniques. Formation of the DNA and RNA triplexes was confirmed from UV-melting and circular dichroic measurements. The interaction process was characterized by increase of thermal melting temperature, perturbation in circular dichroic spectrum and the typical hypochromic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
92
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 47 publications
12
92
0
Order By: Relevance
“…[183][184][185][186] These include tethering of intercalating agents to triplex forming oligionucleotides, photoinduction of covalent cross-links between the third strand and the under lying duplex via a photoactivating agent, use of oligonucleotide analogs with modified bases or intercalating agent that can selectively stabilize the triplexes. Several intercalating ligands 183,[187][188][189][190] are reported to intercalate between the nuclobases of DNA triplexes and improve both stability and sequence specificity of the Hoogsteen base paired third strand. Ren and Chaires 187 have first demonstrated that berberine preferentially and very strongly bound to poly(dT).poly(dA)xpoly(dT) triplex compared to the poly(dA).poly(dT) duplex from novel competition dialysis and thermal melting experiments.…”
Section: A L K a L O I D -T R I P L E X N U C L E I C A C I D S I Nmentioning
confidence: 99%
“…[183][184][185][186] These include tethering of intercalating agents to triplex forming oligionucleotides, photoinduction of covalent cross-links between the third strand and the under lying duplex via a photoactivating agent, use of oligonucleotide analogs with modified bases or intercalating agent that can selectively stabilize the triplexes. Several intercalating ligands 183,[187][188][189][190] are reported to intercalate between the nuclobases of DNA triplexes and improve both stability and sequence specificity of the Hoogsteen base paired third strand. Ren and Chaires 187 have first demonstrated that berberine preferentially and very strongly bound to poly(dT).poly(dA)xpoly(dT) triplex compared to the poly(dA).poly(dT) duplex from novel competition dialysis and thermal melting experiments.…”
Section: A L K a L O I D -T R I P L E X N U C L E I C A C I D S I Nmentioning
confidence: 99%
“…In the present study we report for the first time that all the three alkaloids bind the triplex structure in a cooperative manner. Previous studies on coralyneÀDNA triplex suggested non-cooperative binding [23] [42] [43]. It is likely that the cooperativity phenomenon observed here was missed in previous studies due to the absence of binding data below an r value of 0.2.…”
mentioning
confidence: 59%
“…Conformational changes of the triplex on binding to the alkaloids were investigated from intrinsic CD studies. The intrinsic CD spectra of the T · AT triplex was characterized by a positive band in the region of 275 -285 nm, followed by a hump in the 260 -270-nm region, followed by a large negative band around 245 nm and a bell shaped band in the negative side in the region of 220 -235 nm [23]. The conformation of the triplex was found to be perturbed in presence of all the three alkaloids (Fig.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…They represent small (15 derivatives known) yet intensely studied group of natural products because of their numerous biochemical as well as medical implications e.g. antimicrobial [1], antiinflamatory [2] and antifungal [3] activities, interactions with DNA [4], inhibition of reverse transcriptase [5], inhibition of oxidative burst via affecting NADPH oxidase activity [6] etc. The most common naturally occurring benzophenanthridine alkaloids are sanguinarine and chelerythrine.…”
Section: Introductionmentioning
confidence: 99%